1999
DOI: 10.1148/radiology.211.3.r99jn21829
|View full text |Cite
|
Sign up to set email alerts
|

Cancer in Patients Aged 90 Years or Older: Radiation Therapy

Abstract: Age of 90 years or older is not a limiting factor for radiation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 18 publications
2
29
0
Order By: Relevance
“…Previous studies have found that palliative RT provides effective symptom management and produces little to no toxicity in elderly patients, including those >90 years of age (36)(37)(38)(39)(40)(41)(42)51). Similar results have been found for lung and breast cancer patients receiving curative RT (8,52,53).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Previous studies have found that palliative RT provides effective symptom management and produces little to no toxicity in elderly patients, including those >90 years of age (36)(37)(38)(39)(40)(41)(42)51). Similar results have been found for lung and breast cancer patients receiving curative RT (8,52,53).…”
Section: Discussionsupporting
confidence: 66%
“…There is a need to identify the potential limitations and hazards of palliative RT in the elderly (4,11). Alternatively, some studies have shown that palliative RT provides effective pain management in elderly patients with minimal toxicity in a variety of site groups (36)(37)(38)(39)(40)(41)(42). Consequently, educating physicians on the benefits of palliative RT is recommended to provide equal access to RT for patients of all ages (18).…”
Section: Introductionmentioning
confidence: 99%
“…However standard protocols and/or doses sometimes need to be modified according to patient's conditions or to the onset of complications [65]. As for surgery, age per se does not represent a limiting factor to the prescription of RT [66,67]. …”
Section: Cancer Therapy In the Elderlymentioning
confidence: 99%
“…The treatment of choice should be based on a medical assessment and the preferences of the patient, not on chronological age alone [18] . not be considered a contraindicator for radiation therapy [24][25][26][27][28] . Nevertheless, it has been reported more than a decade ago that elderly patients with HNC recruited in clinical trials had a better performance status compared to those who were not included in clinical trials; therefore, the results from clinical trials might be biased and not generalizable to the general aged HNC population [29] .…”
Section: General Principlesmentioning
confidence: 99%